ACCOUNTING POLICY REGARDING RECOGNITION AND CLASSIFICATION OF FIXED ASSETS ACCORDING TO NATIONAL AND INTERNATIONAL STANDARDS - Кругла, Марина (SWorldJournal, 2024)
The paper examines the importance of accounting policy as a tool for forming a high-quality information system of enterprise management. Noting the important role of fixed assets in the company's activities, a comparative assessment of methodological asp